Autonomic recovery after exercise in trained athletes: Intensity and duration effects - Seiler, S.; Haugen, O.; Kuffel, E. (Medicine & Science in Sports & Exercise, 2007)
Purpose: To investigate the effects of training intensity and duration, through a range representative of training in endurance athletes, on acute recovery of autonomic nervous system (ANS) balance after exercise.